Cost of living and the impact on nursing labour outcomes in NHS acute trusts - Carol Propper; Isabel Stockton; George Stoye (Institute for Fiscal Studies (IFS), 2021)
Retention of nursing staff within the NHS is a key policy issue. Pay policy - and the ability that trusts and nurses have to react to local working conditions and the cost of living - is likely to be a key lever in reducing attrition among current staff. Understanding the restrictions that the current system places on trusts in the face of local cost-of-living changes, and the responses of staff to the decisions made by these trusts, is therefore important in improving staff retention [...] This report examines the effect that variation in the cost of living has on the labour supply of existing nurses in NHS acute trusts. We focus on Band 5 and 6 nurses. These accounted for 23% of the workforce in NHS acute trusts in 2018. We use administrative payroll data from the Electronic Staff Record (ESR) to examine how trusts and nurses react to changes in the local cost of living, and the impact these changes have on the amount of labour supplied by existing nurses.
Keywords: 330